Heart rate variability reflects endoscopic activity and systemic inflammation in patients with Crohn’s disease - Wang, Ruohan; Yan, Fengfeng; Zhang, Hongjie (Frontiers in Medicine, 2026)
PurposeIt is well known that the autonomic nervous system (ANS) activity is impaired in patients with Crohn’s disease (CD). Heart rate variability (HRV), a non-invasive and repeatable measurement, was used to assess ANS activity. The relationships between disease activity and HRV need to be elucidated. Our study also aimed to explore the relationship between HRV parameters and systemic inflammatory biomarkers, and to establish an assessment model using HRV, a non-invasive tool, to assess endoscopic activity in CD.Patients and methodsA total of 84 CD patients (44 active CD and 40 in remission) were enrolled at The First Affiliated Hospital of Nanjing Medical University from January 2022 to December 2022. All patients underwent HRV examination and endoscopy. Clinical data, including demographic variables, disease activity and course, medications, and laboratory data, were collected. Binary logistic regression analysis was used to identify the factors associated with endoscopic activity, based on which the nomogram model was established.ResultsCompared with patients in endoscopic remission, active CD patients had significantly ratio of low frequency to high frequency (LF/HF) (p < 0.001), lower standard deviation of all normal–normal (SDNN) intervals (p = 0.002), and high-frequency HRV (HF) (p = 0.011), suggesting that parasympathetic activity was reduced in active CD patients. In addition, SDNN and HF were negatively correlated with the simple endoscopic score for CD (SES-CD). Meanwhile, HR and LF/HF were found to be independent risk factors for endoscopic disease activity by univariate and binary logistic regression. A regression model was established: HRV assessment of endoscopic active = −8.335 + 0.918LF/HF + 0.084HR (C-index: 0.803, 95% confidence interval [CI]:0.710–0.896).ConclusionThe parasympathetic activity was reduced in active CD patients. Furthermore, the significant correlations between HRV parameters and inflammatory biomarkers underscore that HRV not only reflects endoscopic activity but also mirrors the systemic inflammatory burden in CD. Thus, HRV can potentially be developed into a simple, non-invasive tool for comprehensively assessing disease activity and inflammation in CD.